A comparative analysis of management accounting systems' impact on lean implementation. (1st January 2012) - Li, Xueping; Sawhney, Rapinder; Arendt, Eric John; Ramasamy, Karuppuchamy
Lean principles and practices have been widely adopted by many companies since the early 1990s. These companies are now beginning to realise that traditional costing and accounting methods may hinder the lean initiatives that they are implementing. This raises an important question: "Which cost management and accounting approaches best support the newly implemented lean principles and practices?" This paper examines the relative impact of three different management accounting systems on lean manufacturing implementation through simulation modelling with a single performance metric – net income. Three management accounting alternatives included in this study: traditional management accounting (TMA), activity-based costing (ABC), and value stream costing (VSC). This study compares these three management accounting alternatives using process simulation and statistically designed experimental methods. The results demonstrate that VSC appears to provide a bridge between operational views and financial views of lean, which enhances the transfer of information from shop level to management level.